ANALYSIS OF THE EFFECTIVENESS OF CLEAN WATER DISTRIBUTION MACHINE USING OVERALL EQUIPMENT EFFECTIVENESS (OEE) METHOD - Mail, Abdul; Dahlan, Muhammad; Rauf, Nurhayati; Chairany, A Nurul; Ahmad, Arfandi; Jufri, Khhairunnisa (Center for Study and Journal Management FTI UMI, 2021)
Clean water distribution machines are very important for local drinking water companies to be able to supply clean water to customers. The need for water continues to increase, so an analysis is needed to determine the decline in engine pump performance in the production process. Maintenance activities need to be carried out to maintain the reliability (realiability) of the machine so that it can operate properly. Therefore, a good strategy is needed to maintain the continuity of the production process. The purpose of this research is to measure the performance of the water distribution pump machine / equipment associated with the low level of clean water production, to identify the losses experienced by the company. The Overall Equipment Effectiveness (OEE) value obtained before repairs were carried out in November 2019 for Lapi I was 69.38% and Lapi II was 69. 75% while in December 2019 for Lapi I it was 74.02% and Lapi II was 73.65% still below the JIPM standard, namely ≥85%. From the results of the six big losses, the clean water distribution pump machine as a whole still needs evaluation to make improvements in increasing effectiveness and productivity, especially in the problem of redeuced speed losses so that suggestions can be made to improve the clean water distribution machine. After repairs in January 2020 for Lapi I was 87.90% and Lapi II was 87.26% while in February 2020 for Lapi I it was 90.34% and Lapi II was 85.81%. From the results of the six big losses, the clean water distribution pump machine as a whole still needs evaluation to make improvements in increasing effectiveness and productivity, especially in the problem of redeuced speed losses so that suggestions can be made to improve the clean water distribution machine. After repairs in January 2020 for Lapi I was 87.90% and Lapi II was 87.26% while in February 2020 for Lapi I it was 90.34% and Lapi II was 85.81%. From the results of the six big losses, the clean water distribution pump machine as a whole still needs evaluation to make improvements in increasing effectiveness and productivity, especially in the problem of redeuced speed losses so that suggestions can be made to improve the clean water distribution machine. After repairs in January 2020 for Lapi I was 87.90% and Lapi II was 87.26% while in February 2020 for Lapi I it was 90.34% and Lapi II was 85.81%